ORAL MUCOSITIS IN PATIENTS WITH ACUTE LEUKEMIA UNDERGOING CHEMOTHERAPY AT THE NATIONAL INSTITUTE OF HEMATOLOGY AND BLOOD TRANSFUSION (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the characteristics and prevalence of oral mucositis (OM) in patients with acute leukemia undergoing chemotherapy at the National Institute of Hematology and Blood Transfusion.Methods: A cross-sectional descriptive study was conducted on 301 patients with AL who underwent chemotherapy from January to May 2025. All patients were assessed on day 10 after chemotherapy initiation. The severity of oral mucositis was assessed using the WHO scale.Results: Overall OM incidence was 62,5% (188/301). WHO grades: grade 1, 39,5% (119); grade 2, 20,6% (62); grade 3, 2,3% (7); no grade 4. Most affected sites: buccal mucosa (26,9%), lips (16.9%), tongue (14,0%), palate (13,6%). On day 10, 49,2% had ANC ≤0,5 G/L and 16,9% had platelets ≤20 G/L. Oral hygiene: 87,4% brushed ≥2 times/day; 56,5% performed mucosal cleaning; 0.9% NaCl was most used rinse (39,5%).Conclusion: OM is common in acute leukemia patients receiving chemotherapy, predominantly mild to moderate. Routine oral care, safe mouth-rinse guidance, and close monitoring during neutropenia are essential to prevent and mitigate OM.
Keywords: Acute leukemia, chemotherapy, oral mucositis, nursing care.